Dominasi Opsional Persepsi Mahasiswa Hindu Terhadap Pelaksanaan Yajña Dalam Konteks Kuantitas Dan Kualitas - Anak Agung Gde Oka Widana; Ketut Lisnawati; Anak Agung Sri Sanjiwani; Ni Luh Pasek Sugianti (Jayapangus Press, 2023)
Yajña routines are generally known by the public, especially by Hindus in Bali. However, often the Yajña routine is only seen as a ritual and lacks philosophical understanding. Therefore, it is necessary to conduct further evaluation studies, especially on the understanding of Hindu students in higher education regarding the existence of the Yajña. This research is a field research, with a qualitative descriptive research method. The selection of participants is not directed at the number, but is based on the principles of suitability and adequacy to achieve data saturation. The technique of determining the research subject in this study used purposive sampling, with a psychological approach. The primary data in this study is the result of interviews between researchers and the main resource persons, namely Hindu students of STIKes Wira Medika Bali. Data collection techniques were carried out through interviews, literature and documentation, which were then analyzed using the Colaizzi method. This study aims to transform understanding to the younger generation of Hindus regarding how, what and why the Yajña is carried out. The results showed that the optional dominance of the perception of Hindu students at STIKes Wira Medika Bali towards the implementation of Yajña tends to lead to the context of quantity, which indicates that students tend to more easily understand Yajña in the context of nominal or amount, compared to the quality aspect. This indicates that there is still a need for further improvement of Hindu religious methods and materials, especially in planting an understanding of the existence of Yajña.